Implementasi Pembelajaran Coding Dan Kriptografi Pada Pesan Digital di SMA Negeri 2 Mataram - Maulani Rizqi; Intan Nadilah; Ahmadil Hamdi; Nikken Prima Puspita; I Gede Adhitya Wisnu Wardhana (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service activity aims to increase the understanding of students at State Senior High School 2 Mataram regarding information security by introducing the concepts of coding and cryptography in digital messages. The rapid use of messaging applications among teenagers makes students increasingly vulnerable to cyber threats, necessitating education on how data protection works in online communication. This program is implemented using a descriptive method consisting of planning, implementation, and evaluation stages. The material covered includes basic cryptography concepts, end-to-end encryption mechanisms, and the practical process of the Diffie–Hellman key exchange thru the interactive simulation "Alice and Bob." Learning is designed contextually and participatively so that students can connect theory with the digital applications they use every day. The evaluation results showed an improvement in students' understanding, reflected in their active participation, ability to answer questions, and adequate post-test scores. This activity not only strengthens digital security literacy but also raises students' awareness of the importance of protecting personal data in online communication. This program is expected to be the beginning of more sustainable digital security learning development in the school environment.